PENGEMBANGAN KAIN TENUN IKAT NOWING DAN KEWATEK KECAMATAN WITIHAMA KABUPATEN FLORES-TIMUR - Kristina Eflina Anggo; Donna Isra Silaban (Politeknik Negeri Sriwijaya, 2023)
This article is entitled Preserving Nowing and Kewatek Woven Cloth Arts in Growing Love for Local Culture in Lamabelawa Village, Witihama District, Flores-East Regency. describes the daily problems of the people of Lamabelawa Village in preserving the arts of Nowing and Kewatek woven cloth. There are several studies in this article, namely: I Art as a Local Cultural Identity 2 Describes Nowing woven motifs and offers to be registered with the Trade and Industry Office of East Flores Regency 3. The process of implementing the 4 Packaging Preservation designs in Multimedia. In explaining the discussion of this article, there are several inhibiting factors, namely 1. Many of the next generation of the nation are no longer familiar with the art of woven cloth. 2. Many people do not preserve the arts. Lamabelawa village. Withama District, East Flores Regency is one of the sixteen villages in the Witihama District which is the main entrance gate of the Witihama District. In this article the author tries to explain using descriptive research methods. The author can see firsthand the problems that exist in the location as well as the importance of documentation as evidence of preservation which also encourages a sense of pride in traditional arts in Lamabelawa Village, Witihama District. East Flores Regency.